Metod manual'noi terapii posle sovremennykh operatsii na pozvonochnike i vozmozhnost ego primeneniya v sportivnoi praktike - Nikolayev, S. L. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The use of the manual therapy method after modern spinal column operations is explained under the aspect of its possible use in sport practice.